ANALISIS PENGARUH INDEPENDENSI, KOMPETENSI DAN AKUNTANBILITAS AUDITOR INTERNAL TERHADAP KUALITAS HASIL AUDIT (Survei Auditor Internal di Pemprov DKI Jakarta) - Harry Dwirendra; Susi Dwimulyani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2016)
The objectives are: 1) To determine the effect of independence on the quality of the audit results. 2) To determine the effect of competence on the quality of the audit results. 3) Accountability To determine the effect on the quality of the audit results. This study used a survey method explanatory. Data collection techniques consist of Field Research (Field Research): Structured interviews, Interviews tersruktur and questionnaire methods, techniques of collecting primary data by distributing questionnaires to the respondents intended. Research Library (Library Research). Target population in this study is the senior internal auditor in the city government totaling 148. Techniques used in sampling is the technique of random sampling (simple random sampling). With the formula slovin the sample size in this study is as much as 108 samples. Based on the results of the discussion in which (1) the partial hypothesis testing showed a significant difference to the quality of audit independence (2) partial hypothesis testing showed a significant difference to the quality of the audit competence. (3) Based on the partial hypothesis testing showed a significant difference to the quality of the audit accountability.